Integrating Health Promotion into Preschool Education: Evidence from an Action Research Internship - Couto, Filipe; Silva, Ana Isabel (JOYCED: Journal of Early Childhood Education, 2025)
Early childhood education plays a key role in establishing healthy lifestyle habits; however, health-related domains such as nutrition, hygiene, physical activity, and socio-emotional learning are often addressed in a fragmented manner in preschool settings. This study aimed to design, implement, and analyze a health promotion intervention in a Portuguese preschool, examining its contribution to children’s health-related knowledge and behaviors, as well as to the professional development of the intern educator. The study was conducted as part of a professional higher technical internship in Child and Youth Care and adopted an action research methodology. Cycles of planning, action, observation, and reflection guided the implementation of the Healthy Life project, which comprised seven structured, play-based activities focused on nutrition, hygiene, physical activity, and socio-emotional regulation. Data was collected through systematic participant observation, field notes, photographic documentation, and reflective journals. Observational data indicated improvements in children’s ability to identify healthy and less healthy foods, describe basic hygiene procedures, and express emotions using appropriate vocabulary. Behavioral indicators included more frequent spontaneous handwashing before meals, peer reminders of hygiene routines, and increased requests for water instead of sweetened beverages during snack time. Group-based activities were associated with enhanced cooperation, turn-taking, and empathetic responses among peers. The findings suggest that preschools are effective contexts for promoting healthy lifestyles when health education is integrated into daily routines and supported by reflective teaching practices. The study highlights the importance of educator training, institutional support, and family involvement to sustain health-promoting behaviors in early childhood education.